Defining ecological restoration of peatlands in Central Kalimantan, Indonesia - Puspitaloka, D.; Kim, Y-S.; Purnomo, H.; Fulé, P.Z. (Wiley, 2020)
Indonesia declared an ambitious plan to restore its degraded and fire‐prone peatlands, which have been a source of significant greenhouse gas and haze. However, the progress has been slow and the plan cannot succeed without sustained social supports and political will. Although many previous studies argued for the need to see ecological restoration in socio‐economic contexts, empirical assessments have been lacking for how restoration is operationalized on the ground. We interviewed 47 key informants involved in four different projects in Central Kalimantan, Indonesia, and assessed their definitions, goals, and practices of peatland restoration. Most of the actors we interviewed defined peatland restoration primarily in an ecological context following the global concept of ecological restoration. However, all four restoration projects were designed without determining reference and trajectory conditions. Their intermediate goals and practices were more focused on engaging local communities and developing sustainable livelihood options than improving the ecological conditions of peatlands. To be internally consistent, peatland restoration needs to recognize a social dimension in its process, as well as in its goal. Setting clear trajectory conditions is also important to clarify achievable goals and measurable intermediate outcomes. We propose the following definition of peatland restoration: a process of assisting the recovery of degraded peatland ecosystems to achieve the appropriate trajectories defined through multi‐stakeholder collaboration within social‐ecological contexts. We hope to generate healthy debates to further refine the definition that encompasses both social and ecological dimensions to generate broader support for sustaining and expanding peatland restoration projects in Indonesia.